Changes in cuticle compositions and crystal structure of 'Bingtang' sweet orange fruits (Citrus sinensis) during storage. Issue 1 (1st January 2018) - Ding, Shenghua; Zhang, Ding; Wang, Rongrong; Ou, Shiyi; Shan, Yang
ABSTRACT: Changes in composition and structure of orange cuticle during storage at 4°C or 25°C for 40 days were investigated. The total epicuticular wax content of fruits increased during storage at 4°C for 30 days and then decreased as storage time prolonged to 40 days, while it increased continuously at 25°C for 40 days. The total intracuticular wax content of fruits increased to 9.70 μg cm −2 stored at 4°C for 10 days and then decreased to 6.74 μg cm −2 for 40 days. The total intracuticular wax content of fruits was decreased to 5.17 μg cm −2 stored at 25°C for 10 days and then increased to 10.06 μg cm −2 for 30 days. Fatty acids were the most abundant component of the epicuticular wax and terpenoids were restricted to the intracuticular wax. Terpenoids were restricted to the intracuticular wax, and their amounts in the fruit stored at 4°C increased continuously during the first 20 days of storage at 4°C and then decreased as storage time increased up to 40 days. Although significant changes were found in the contents of the cutin monomer, their proportions did not change significantly during storage at 4°C or 25°C. Size of wax platelets crystals wax increased during storage of fruits at 4°C up to 30 days; however, the crystals were degraded and decreased as storage prolonged to 40 days. Furthermore, the shape of the fruit cuticle surface wax crystals changed from flattened platelets to small granulelike after storage at 25°C for 20–40 days. The obtained results provide detailed information about the changes in orange cuticle occur during storage at varying temperatures, which may help in preserving the quality of citrus fruits during storage.